INCLUSIVE EDUCATION FOR UNLEASHING THE TALENTS OF PERSONS WITH DISABILITIES (Interdisciplinary Studies Journal, 2024)
Recurrently, many Brazilians are born or become, through some fatality, people with disabilities. This requires the development of strategies and actions to ensure their equal rights. In this direction, the research aimed to identify and analyze the legal aspects of Law No. 13.146/2015, in relation to education, and reflect on its effectiveness from recent research on the subject. For the data analysis, the content analysis was chosen. The results showed that there is still a lot of work to be done in order to realize the rights expressed in the legislation, such as the development and implementation of public policies that welcome people with disabilities in their entirety. We emphasize that legislation is an essential step for the educational inclusion of people with disabilities, but many other barriers need to be broken down, including prejudice.
Keywords: Inclusive Education; Status of people with disabilities; Right to education